Analysis of power losses and experimental method for determining resistance in electric elevators - Đokić, Radomir (Strojniški vestnik, 2024)
To be able to carry out a high-quality analysis of the operation and design of elevator systems with a driving pulley, it is necessary to determine the size of the losses that occur in the drive mechanism and elevator guide rails. The paper defines an experimental procedure for determining the losses and the efficiency coefficient of elevator facilities depending on the relative load of the cabin in operational conditions. The experiment was carried out on a passenger elevator with a rated load of 320 kg and a lifting height of 28 m. An analysis of the resistance, i.e., the source of power losses in vertical lifting devices, was performed, the most significant of which occur and are especially pronounced in worm gear reducers and on the guiding system of the cabin and counterweight, where the type of guiding elements also has an influence. A particular problem is expressed due to the changing state of the contact surfaces (between the guide rails and the guide shoes) during exploitation and the eccentric loading of the cabin. Also, the paper analysed the obtained measurement results to determine the dependence of the efficiency coefficient of the facility concerning the relative load of the cabin.
Keywords: določitev izkoristka; driving mechanism resistances; efficiency determination; electric elevators; električna dvigala; guide rails resistances; upor pogonskega mehanizma; upor vodilnih tirnic